From Loose to Tight Management Seeking Evidence of Archetype Change in Dutch and English Higher Education - Weyer, Elke (Organization & Public Management,, 2018)
Elke Weyer sheds light on the question why, after more than three decades of higher education reforms in some countries, it is still not clear whether the reforms have achieved their stated goals, i.e., to create autonomous universities that meet political expectations. By back-casting real-life decision-making processes, the author reconstructs how different types of actors influenced the academic governance of higher education institutions in the context of these reforms. This approach highlights how numerous changes in governance and organisation affect the relationships between actors and how they promote their interests. Contents The Transformation of the University - Reality or Myth? Actor-Centered Institutionalism Building the Archetype Template Seeking Evidence of Archetype Change in Dutch Higher Education Seeking Evidence of Archetype Change in English Higher Education Target Groups Researchers and students in the field of sociology with a focus on science studies, university research and organisational studies, political scientists Managers of higher education institutions The Author Elke Weyer works at the head office of the German Council of Science and Humanities, Cologne, Germany.